America's Lab Report: Investigations in High School Science - National Research Council (The National Academies Press, 2006)
Laboratory experiences as a part of most U.S. high school science curricula have been taken for granted for decades, but they have rarely been carefully examined. What do they contribute to science learning? What can they contribute to science learning? What is the current status of labs in our nation00ef00bf00bds high schools as a context for learning science? This book looks at a range of questions about how laboratory experiences fit into U.S. high schools: What is effective laboratory teaching? What does research tell us about learning in high school science labs? How should student learning in laboratory experiences be assessed? Do all student have access to laboratory experiences? What changes need to be made to improve laboratory experiences for high school students? How can school organization contribute to effective laboratory teaching? With increased attention to the U.S. education system and student outcomes, no part of the high school curriculum should escape scrutiny. This timely book investigates factors that influence a high school laboratory experience, looking closely at what currently takes place and what the goals of those experiences are and should be. Science educators, school administrators, policy makers, and parents will all benefit from a better understanding of the need for laboratory experiences to be an integral part of the science curriculum2014and how that can be accomplished.

Systems for State Science Assessment - National Research Council (The National Academies Press, 2006)
In response to the No Child Left Behind Act of 2001 (NCLB), Systems for State Science Assessment explores the ideas and tools that are needed to assess science learning at the state level. This book provides a detailed examination of K-12 science assessment: looking specifically at what should be measured and how to measure it. Along with reading and mathematics, the testing of science is a key component of NCLB2014it is part of the national effort to establish challenging academic content standards and develop the tools to measure student progress toward higher achievement. The book will be a critical resource for states that are designing and implementing science assessments to meet the 2007-2008 requirements of NCLB. In addition to offering important information for states, Systems for State Science Assessment provides policy makers, local schools, teachers, scientists, and parents with a broad view of the role of testing and assessment in science education.

ICT Fluency and High Schools: A Workshop Summary - National Research Council (The National Academies Press, 2006)
Information and communications technology (ICT) pervades virtually all domains of modern life2014educational, professional, social, and personal. Yet although there have been numerous calls for linkages that enable ICT competencies acquired in one domain to benefit another, this goal has largely remained unrealized. In particular, while technology skills and applications at work could be greatly enhanced by earlier complementary learning at school2014particularly in K-12 education, a formative and influential stage in a person's life2014little progress has been made on such linkages. At present, the curricula of most U.S. high schools focus on skills in the use of tools such as specific word-processing software or contemporary Internet search engines. Although these kinds of skills are certainly valuable2014at least for a while2014they comprise just one component, and the most rudimentary component, of ICT competencies. The National Academies held a workshop in October 2005 to address the specifics of ICT learning during the high school years would require an explicit effort to build on that report. The workshop was designed to extend the work begun in the report Being Fluent with Information Technology, which identified key components of ICT fluency and discussed their implications for undergraduate education. ICT Fluency and High Schools summarizes the workshop, which had three primary objectives: (1) to examine the need for updates to the ICT-fluency framework presented in the 1999 study; (2) to identify and analyze the most promising current efforts to provide in high schools many of the ICT competencies required not only in the workplace but also in people's day-to-day functioning as citizens; and (3) to consider what information or research is needed to inform efforts to help high school students develop ICT fluency.

Learning to Think Spatially - National Research Council (The National Academies Press, 2006)
Learning to Think Spatially examines how spatial thinking might be incorporated into existing standards-based instruction across the school curriculum. Spatial thinking must be recognized as a fundamental part of K201312 education and as an integrator and a facilitator for problem solving across the curriculum. With advances in computing technologies and the increasing availability of geospatial data, spatial thinking will play a significant role in the information-based economy of the twenty-first century. Using appropriately designed support systems tailored to the K201312 context, spatial thinking can be taught formally to all students. A geographic information system (GIS) offers one example of a high-technology support system that can enable students and teachers to practice and apply spatial thinking in many areas of the curriculum.

To Recruit and Advance: Women Students and Faculty in Science and Engineering - National Research Council (The National Academies Press, 2006)
Although more women than men participate in higher education in the United States, the same is not true when it comes to pursuing careers in science and engineering. To Recruit and Advance: Women Students and Faculty in Science and Engineering identifies and discusses better practices for recruitment, retention, and promotion for women scientists and engineers in academia. Seeking to move beyond yet another catalog of challenges facing the advancement of women in academic science and engineering, this book describes actions actually taken by universities to improve the situation for women. Serving as a guide, it examines the following: Recruitment of female undergraduates and graduate students. Ways of reducing attrition in science and engineering degree programs in the early undergraduate years. Improving retention rates of women at critical transition points2014from undergraduate to graduate student, from graduate student to postdoc, from postdoc to first faculty position. Recruitment of women for tenure-track positions. Increasing the tenure rate for women faculty. Increasing the number of women in administrative positions. This guide offers numerous solutions that may be of use to other universities and colleges and will be an essential resource for anyone interested in improving the position of women students, faculty, deans, provosts, and presidents in science and engineering.

Tech Tally: Approaches to Assessing Technological Literacy - National Academy of Engineering; National Research Council (The National Academies Press, 2006)
In a broad sense, technology is any modification of the natural world made to fulfill human needs or desires. Although people tend to focus on the most recent technological inventions, technology includes a myriad of devices and systems that profoundly affect everyone in modern society. Technology is pervasive; an informed citizenship needs to know what technology is, how it works, how it is created, how it shapes our society, and how society influences technological development. This understanding depends in large part on an individual level of technological literacy. Tech Tally: Approaches to Assessing Technological Literacy determines the most viable approaches to assessing technological literacy for students, teachers, and out-of-school adults. The book examines opportunities and obstacles to developing scientifically valid and broadly applicable assessment instruments for technological literacy in the three target populations. The book offers findings and 12 related recommendations that address five critical areas: instrument development; research on learning; computer-based assessment methods, framework development, and public perceptions of technology. This book will be of special interest to individuals and groups promoting technological literacy in the United States, education and government policy makers in federal and state agencies, as well as the education research community.

Review and Assessment of the Health and Productivity Benefits of Green Schools: An Interim Report - National Research Council (The National Academies Press, 2006)
Some educational professionals have suggested that so-called green schools would result in superior performance and increased health for students and teachers. While there is no commonly accepted definition of a green school, there are a number of attributes that such schools appear to have: low cost operations, security, healthy and comfortable, and an environment that enhances learning are among them. To determine the health and productivity benefits of green schools, the Massachusetts Technology Collaborative, the Barr and Kendall Foundations, the Connecticut Clean Energy Fund, and the U.S. Green Building Council asked the NRC to examine available studies about the effects of green schools on student learning and teacher productivity. This interim report presents an evaluation of evidence for relationships between various health, learning, and productivity outcomes and five characteristics of green schools: the building envelope, ventilation, lighting, acoustics, and condition. The final report will present evaluations for additional characteristics, a synthesis of the results of all assessments, and promising areas of research.

Engineering Studies at Tribal Colleges and Universities - National Academy of Engineering (The National Academies Press, 2006)
This study was designed to provide expert, objective, independent advice to 11 tribal colleges that are working together to offer engineering programs. The chief data-gathering activity was a one and one-half day workshop. Reasons for establishing a four-year engineering program at a TCU were outlined in the workshop2014making it possible for American Indian students to complete a four-year engineering degree entirely within the tribal college system; reducing the high attrition rate of American Indian students who attend mainstream educational institutions; and providing an engineering program that is culturally relevant to tribal students.

Critical Technology Accessibility - National Research Council (The National Academies Press, 2006)
In 2003, the Defense Intelligence Agency asked the NRC to form a standing committee to help develop study topics about technology warning. One issue that was identified was the growing dependence on foreign suppliers of critical technology as a result of the increase in globalization of economic activity. Two important questions emerged for study: what is the risk of denial of critical products from foreign sources and what must the United States do to assure access to future critical products and technologies? This report presents an assessment addressing those two questions. It also provides an analysis of a strategic approach to manage the consequences of this trend towards increased globalization. Finally, the report offers a set of recommendations to implement this strategy and to increase assurance of access to critical technologies.

Issues Affecting the Future of the U.S. Space Science and Engineering Workforce: Interim Report - National Research Council (The National Academies Press, 2006)
In January 2006, the President announced a new civilian space policy focusing on exploration. As part of its preparations to implement that policy, NASA asked the NRC to explore long-range science and technology workforce needs to achieve the space exploration vision, identify obstacles to filling those needs, and put forward solutions to those obstacles. As part of the study, the NRC held a workshop to identify important factors affecting NASA's future workforce and its capacity to implement the exploration vision. This interim report presents a summary of the highlights of that workshop and an initial set of findings. The report provides a review of the workforce implications of NASA's plans, an assessment of science and technology workforce demographics, an analysis of factors affecting the aerospace workforce for both NASA and the relevant aerospace industry, and preliminary findings and recommendations. A final report is scheduled for completion in early 2007.

Ensuring an Infectious Disease Workforce: Education and Training Needs for the 21st Century: Workshop Summary - Institute of Medicine (The National Academies Press, 2006)
The Forum on Microbial Threats (previously named the Forum on Emerging Infections) was created in 1996 in response to a request from the Centers for Disease Control and Prevention (CDC) and the National Institutes of Health (NIH). The goal of the Forum is to provide structured opportunities for representatives from academia, industry, professional and interest groups, and government to examine and discuss scientific and policy issues that are of shared interest and that are specifically related to research and prevention, detection, and management of emerging infectious diseases. In accomplishing this task, the Forum provides the opportunity to foster the exchange of information and ideas, identify areas in need of greater attention, clarify policy issues by enhancing knowledge and identifying points of agreement, and inform decision makers about science and policy issues. The Forum seeks to illuminate issues rather than resolve them directly; hence, it does not provide advice or recommendations on any specific policy initiative pending before any agency or organization. Its strengths are the diversity of its membership and the contributions of individual members expressed throughout the activities of the Forum. Recent increased attention to both United States and international public health systems as well as the medical research and treatment infrastructure has revealed significant deficiencies in their capacity to respond to infectious diseases. Medical and public health professionals may be poorly equipped to detect, diagnose, and treat common infectious diseases as well as those diseases that pose an unexpected threat. The need for the development of domestic and international training programs in the expanding field of emerging and reemerging infectious diseases is well recognized. Well-trained infectious disease professionals form the basis of a strong national healthcare system. The Forum on Emerging Infections (now renamed the Forum on Microbial Threats) convened a 2-day workshop discussion2014the subject of this summary2014to examine the education and training needs to ensure an adequate infectious diseases workforce. The workshop reviewed trends in research training programs and discussed the requirements for establishing successful educational initiatives and training programs to ensure a competent and prepared workforce for current and future challenges in infectious diseases. Some key disciplines explored as case-study examinations included infectious disease epidemiology, vaccinology, vector biology, and public health laboratorians.

Biological, Social, and Organizational Components of Success for Women in Academic Science and Engineering: Report of a Workshop - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2006)
During the last 40 years, the number of women studying science and engineering (S&E) has increased dramatically. Nevertheless, women do not hold academic faculty positions in numbers that commensurate with their increasing share of the S&E talent pool. The discrepancy exists at both the junior and senior faculty levels. In December 2005, the National Research Council held a workshop to explore these issues. Experts in a number of disciplines met to address what sex-differences research tells us about capability, behavior, career decisions, and achievement; the role of organizational structures and institutional policy; cross-cutting issues of race and ethnicity; key research needs and experimental paradigms and tools; and the ramifications of their research for policy, particularly for evaluating current and potential academic faculty. Biological, Social, and Organizational Components of Success for Women in Academic Science and Engineering consists of three elements: an introduction, summaries of panel discussions including public comment sessions, and poster abstracts.